JEWISH ASSOL’S WEDDING PLAN, OR ESHET HAIAL BREAKS THE WALLS: AN EXCELLENT WOMAN IN RAMA BURSHTEIN’S LAAVOR AT HA-KIR - ZISELMAN, Boris; USTYUZHYN, Igor (Accents and Paradoxes of Modern Philology, 2022)
The article is devoted to American Israeli haredi director Rama Burshtein’s second film Laavor et ha-Kir (הקיר את לעבור,’ to break through the wall’, Ivrit; in the US: The Wedding Plan, 2016). The first part of the article (dealing with the conscious part of the author’s mind) is an attempt to reveal and explain the most important biblical and rabbinic sources that the film is based upon. Burshtein’s protagonist, Michal, is an Orthodox Jewish yerushalmi spinster in her thirties that desperately wants to get married. She is an active, brave and resourceful lady of faith that represents the best Jewish values. Michal is obviously the chossid חיל אשת) woman of valour, Prov. 31:10), but, for some strange reason, God does not send her a husband. The excellent wife goes far to get bread (Prov. 31:14), and, likewise, Michal goes as far as her religion allows her (a matchmaker, a healer, Ukraine) to get a great husband, even if it requires a miracle. “A great miracle was here” in the 2d century B.C.E. for the Macabean rebels and Michal expects a (relatively) small one to happen for her at the same place at the same time 22 centuries later. What she needs to do is to make sure that she has done her part of the job and that she is 100 per cent ready. The second part of the article follows G. K. Chesterton’s advice to the critics not to spend much time dealing with the conscious part of the author’s mind (”which the author himself can express”) but to deal with the subconscious part of the author’s mind and say about the author “the very things that would have made him jump out of his boots.” So, as Ashkenazim came out not only from Egypt, but also from Poland / Ukraine (S. Freud, P. Wexler, М. Dorfman), the critics suggest that in 2016 the Burshteins (cf. burshtyn and bursztyn, amber, in Ukrainian and Polish) staged the modern Jewish version of Scarlet Sails, the Christian feieria composed by the ethnic Pole Aleksandr Grinevski а hundred years earlier. Michal is today’s dati Israeli Assol’. Even if Rama Burshtein is not familiar with A. S. Grin, the argument still stands: the Spirit blows where she wants to make sure that between the true artists of any time there is an unconscious community (T. S. Eliot).